POSS Polyimide Sealed Flexible Triple‐Junction GaAs Thin‐Film Solar Cells for Space Applications (Adv. Mater. Technol. 12/2021). Issue 12 (9th December 2021) - Qian, Min; Mao, Xiaojun; Wu, Min; Cao, Zhangyi; Liu, Qing; Sun, Lijie; Gao, Yang; Xuan, Xiaoyang; Pan, Yu; Niu, Yueping; Gong, Shangqing
Abstract : Thin‐Film Solar Cell Min Qian, Min Wu, and co‐workers introduce a flexible triple‐junction GaAs thin‐film solar cell in article 2100603 . The cell is sealed by POSS polyimide films by a thermal lamination process, which exhibits a high photoelectric efficiency of 28.44% (AM0, 25 °C) and is durable under space irradiation environment, showing promising potentials in flexible, lightweight, integration for durable high‐efficiency power supplies in low and high Earth orbits.